Lessons from the five data breaches: Analyzing framed crisis response strategies and crisis severity - Bokyung Kim; Kristine Johnson; Sun-Young Park (Cogent Business & Management, 2017)
To fill a gap of research that explores cyber crisis management, this study analyzed news stories of the five largest data breaches experienced in 2014 by retailers (i.e. Target, Michaels, Neiman Marcus, Home Depot, and Staples). Corporate crisis communication and its news coverage (n = 64) were evaluated for crisis communication strategies and framed situational factors. Despite companies’ use of multiple strategies, newspapers reported their use of advocate strategies more often. Massmediated crisis response strategies were even different among the five companies. Newspapers also reframed crisis severity and crisis controllability. Finally, our findings addressed the key to dealing with the public relations nightmare that would result from a security breach.